Untraditional Methods Of Obtaining Nationality In Jordanian Legislation (A Comparative Study) Preparation (Journal of Namibian Studies : History Politics Culture, 2023)
This research dealt with non-traditional methods of acquiring nationality in Jordanian legislation compared to legislation that included texts and situations that address the granting of nationality in exceptional ways -  other than the region and blood - such as granting citizenship in order to encourage investment, and giving citizenship to creative and distinguished people in various fields ... Etc. where the problem of the research was the lack of unity of Jordanian laws and adequacy to address the acquisition  of nationality in exceptional ways and the research concluded that the  Jordanian legislator stipulated the granting of nationality in exceptional ways and set terms and conditions, but scattered texts and multiple legislation and recommended the study that the nationality law includes all cases under which citizenship is granted by non-traditional ways.